Sulfide all-solid-state battery silicon alloy negative electrode and preparation method and application thereof

By using silicon alloy negative electrode material in sulfide all-solid state batteries, the internal stress and conductivity problems caused by volume changes in the silicon negative electrode are solved, and high magnification and long cycle stability are achieved.

CN119920850APending Publication Date: 2025-05-02XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202510117272.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The silicon negative electrode causes structural damage due to internal stress caused by volume changes in sulfide all-solid state batteries, and the low conductivity and ion diffusion coefficient lead to the difficulty in exerting capacity under large current density.

Method used

Using the preparation method of silicon alloy negative electrode material, metal powder, silicon powder and phosphorus powder are mixed and alloyed by mechanical ball milling, conductive additives and binders are added, negative electrode slurry is prepared and coated on the current collector to form a silicon alloy negative electrode sheet.

Benefits of technology

By introducing metal and phosphorus elements, the crystal plane spacing of silicon is widened, the carrier transmission rate is improved, the lithium ion diffusion coefficient and electron conductivity are enhanced, the internal stress failure of the negative electrode is reduced, the battery life is extended, and high magnification and long cycle stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920850A_ABST
    Figure CN119920850A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide all-solid-state battery silicon alloy negative electrode and a preparation method and application thereof, and belongs to the technical field of all-solid-state batteries. The slurry coated on the surface of the alloy negative electrode contains a negative electrode active material silicon alloy (metal-Si-P), and the silicon alloy negative electrode active material is prepared by a mechanical ball milling method, is simple to operate, is green and environment-friendly, and is suitable for large-scale preparation. The silicon alloy negative electrode active material can remarkably improve the electron conductivity and the ion diffusion coefficient of a negative electrode, meanwhile, stress damage caused by negative electrode volume change is relieved, the electrode structure stability is maintained, and stable long circulation of a sulfide all-solid-state battery is achieved. The invention also provides application of the silicon alloy negative electrode of the sulfide all-solid-state battery, and when the negative electrode is applied to the sulfide all-solid-state battery, good long cycle performance and rate capability can be brought to the sulfide all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state batteries and relates to a sulfide all-solid-state battery silicon alloy negative electrode and a preparation method and application thereof. Background Art

[0002] With the rise of electric vehicles and the increase in people's environmental awareness, higher requirements have been put forward for the energy storage field, especially lithium-ion batteries, especially for the safety performance, energy density and power density of lithium-ion batteries. However, since the energy density of the current liquid lithium-ion battery system is close to the theoretical limit, and because the use of organic electrolytes is prone to fire and explosion and other safety hazards, it cannot meet people's current needs. Therefore, it is necessary to develop a new battery system to adapt to the development of the energy storage field.

[0003] All-solid-state batteries have excellent safety, higher energy density and power density because they use solid electrolytes instead of organic electrolytes, and have become a research hotspot in the field of energy storage. Compared with oxide solid electrolytes and composite solid electrolytes, sulfide solid electrolytes have become one of the key research objects in the development of all-solid-state batteries due to their high ionic conductivity and excellent mechanical properties. Silicon anode has a high theoretical specific capacity (3579 mAh / g) and a moderate lithium insertion potential (~0.4 V vs. Li + / Li) inhibits the growth of lithium dendrites. At the same time, as the second most abundant element on earth, it has the characteristics of low cost and wide source. Therefore, it is very promising to realize sulfide all-solid-state batteries with high energy density and power density. However, the large volume change of silicon during the process of lithium extraction / insertion (~300%) will produce huge internal stress, causing vertical cracks inside the silicon negative electrode, thereby increasing the curvature of the lithium ion transmission path and increasing the internal resistance of the battery. As the battery continues to operate, it will eventually lead to battery failure. At the same time, the lower electrical conductivity and ion diffusion coefficient of silicon will also make it difficult for the silicon negative electrode to exert its capacity at high current density. These two problems hinder the application of silicon negative electrodes in sulfide all-solid-state batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a sulfide all-solid-state battery silicon alloy negative electrode and a preparation method and application thereof, so as to solve the problem in the prior art that the internal stress generated by the volume change of the silicon negative electrode causes the negative electrode structure to be destroyed, and the lower electrical conductivity and ion diffusion coefficient of silicon make it difficult for the negative electrode to exert its capacity at a higher current density.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode comprises the following steps: Step 1, mixing metal powder, silicon powder and phosphorus powder and then ball milling to obtain a negative electrode active material; the metal powder is any one of zinc powder, copper powder, aluminum powder or indium powder or a mixture of several thereof; Step 2, mixing the negative electrode active material and the conductive additive, and obtaining a mixed powder of the conductive additive and the negative electrode active material after ball milling; Step 3, adding a binder and a solvent to the mixed powder obtained in step 2 to obtain a mixture, and ball-milling the mixture to obtain a uniform negative electrode slurry; Step 4: coating the negative electrode slurry on the surface of the current collector, drying and cutting to obtain a silicon alloy negative electrode sheet.

[0006] A further improvement of the present invention is: Preferably, in step 1, the mixing molar ratio of the metal powder, silicon powder and phosphorus powder is (1-4): (2-12): (2-3).

[0007] Preferably, in step 1, when the metal powder consists of two or more types of metals, they are mixed in an equimolar ratio.

[0008] Preferably, in step 1, the ball milling time is 10-15 h, and the rotation speed is 450-800 rpm.

[0009] Preferably, in step 1, the silicon powder is nano silicon or micro silicon.

[0010] Preferably, in step 2 and step 3, the mixing mass ratio of the negative electrode active material, the conductive additive and the binder is (8-9): (1-0.5): (1-0.5).

[0011] Preferably, in step 4, the loading amount of the negative electrode slurry on the current collector is 0.4-2 mg / cm 2 The current collector is copper foil, and the coating thickness of the negative electrode slurry is 60 to 300 μm.

[0012] Preferably, in step 2, the conductive additive is graphite, conductive carbon black, carbon fiber, carbon nanotube or graphene, and in step 3, the binder is polyacrylic acid, polyvinylidene fluoride or styrene-butadiene rubber.

[0013] A sulfide all-solid-state battery silicon alloy negative electrode prepared by the above preparation method comprises a current collector, on which a negative electrode slurry is coated, wherein the negative electrode slurry is composed of a negative electrode active material, a binder and a conductive additive; the negative electrode active material is obtained by mechanical ball milling and alloying of metal powder, silicon powder and phosphorus powder; The metal is any one of zinc, copper, aluminum or indium or a mixture of several of them.

[0014] An application of the above-mentioned sulfide all-solid-state battery silicon alloy negative electrode is used in a sulfide all-solid-state battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a silicon alloy negative electrode material for a sulfide all-solid-state battery. In the preparation process, firstly, the negative electrode active material is obtained by mechanical ball milling, then the negative electrode active material is mixed with a conductive additive, a binder and a solvent by mechanical ball milling to obtain a negative electrode slurry, and finally the negative electrode slurry is coated on a current collector and dried to obtain an electrode sheet; wherein the negative electrode active material is a silicon alloy, which is obtained by mixing metal powder, silicon powder and phosphorus powder and then ball milling, wherein the metal powder is any one of zinc powder, copper powder, aluminum powder and indium powder or a mixture of several thereof; the preparation method and the composition of the negative electrode slurry have the following advantages: (1) Phosphorus is introduced into the negative electrode active material as an alloying element. The introduction of metal elements and alloying elements effectively widens the interplanar spacing of silicon and increases the carrier transfer rate, thereby significantly improving the electronic conductivity and lithium ion diffusion coefficient of the silicon negative electrode, which is beneficial to reducing the lithium ion concentration gradient inside the negative electrode, alleviating the internal stress damage of the negative electrode, and extending the battery life.

[0016] (2) When the metal elements include two or more, the multiple alloy elements make the entire negative electrode active material have an entropy increase effect, making the electrochemical performance of the negative electrode active material better.

[0017] (3) Unlike pure silicon, which becomes amorphous after lithiation and delithiation, this alloy can maintain its crystal structure during lithiation and delithiation. This reversible change in crystal structure can effectively reduce the damage to the electrode material during lithium ion insertion and extraction, and alleviate the volume expansion of the electrode during battery cycling, thereby maintaining the stability of the electrode structure. At the same time, this reversible crystal structure is also conducive to maintaining high reaction kinetics during battery operation. Ultimately, high rate and long cycle stability of silicon-based solid-state batteries can be achieved.

[0018] (4) Metal elements and phosphorus elements are introduced into silicon through mechanical ball milling to form a silicon alloy, and the crystal structure of silicon is transformed from a diamond structure to a sphalerite structure, so that the Young's modulus of the silicon alloy is significantly reduced to 2.0-2.7 GPa compared with silicon (10.0-11.6 GPa). This reduced Young's modulus enhances the material's ability to adapt to volume changes and can effectively alleviate stress damage caused by lithium ion extraction / insertion, thereby further improving the stability of the electrode structure and achieving long-cycle stability of sulfide all-solid-state batteries.

[0019] The present invention also discloses a sulfide all-solid-state battery silicon alloy negative electrode, in which the slurry coated on the surface of the current collector contains a metal-Si-P alloy, wherein the metal element is one or several metal elements; by introducing the metal element and the P element, the interplanar spacing of silicon is widened, thereby improving the carrier transmission rate. At the same time, the alloy active material also has a reversible crystal structure change, reducing the damage to the electrode material during the lithium ion deintercalation process, and alleviating the stress problem caused by volume expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD spectra of Example 1, Comparative Example 2 and Comparative Example 3 of the present invention are shown in FIG.

[0021] Figure 2 These are SEM and EDS spectra of the alloy particles uniformly mixed with graphite prepared in Example 1 of the present invention.

[0022] Figure 3 It is a long cycle performance diagram of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0023] Figure 4 This is a comparison chart of the electronic conductivity of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0024] Figure 5 This is a comparison chart of the lithium ion diffusion coefficients of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0025] Figure 6 The XRD spectra of Example 4, Comparative Example 4 and Comparative Example 5 of the present invention are shown in FIG.

[0026] Figure 7 These are SEM and EDS spectra of the alloy particles uniformly mixed with graphite prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0028] In this document, all characteristics such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be regarded as In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercially available products, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0030] The first aspect of the present invention discloses a sulfide all-solid-state battery silicon alloy negative electrode, comprising a current collector and a negative electrode slurry coated on the current collector; the negative electrode slurry is composed of a negative electrode active material, a binder and a conductive additive, the negative electrode active material is a silicon alloy, and the silicon alloy is obtained by mechanical ball milling alloying of metal elements, red phosphorus (P) and silicon (Si).

[0031] The metal element is any one of zinc (Zn), copper (Cu), aluminum (Al) and indium (In) or a mixture of several metal elements, and P is used as an alloying element. When there are two or more metal elements, the metal elements are mixed in equal moles.

[0032] In some embodiments of the present invention, the mass ratio of the negative electrode active material, the binder and the conductive additive is (8-9): (1-0.5): (1-0.5).

[0033] As a preferred solution, the ratio of negative electrode active material: conductive additive: binder is 8:1:1.

[0034] Preferably, the current collector is a copper foil with a thickness of 12 μm.

[0035] Preferably, the binder is polyacrylic acid, polyvinylidene fluoride or styrene-butadiene rubber.

[0036] Preferably, the conductive additive is graphite, conductive carbon black, carbon fiber, carbon nanotube or graphene.

[0037] Preferably, the molar ratio of metal element, Si and P is (1-4): (2-12): (2-3).

[0038] Exemplarily, the molar ratio of the metal element to Si may be 1:2, 1:7 or 1:12.

[0039] For example, the molar ratio of Si to the alloying promoting element may be 2:3, 7:3, or 12:3.

[0040] Preferably, the negative electrode active material is a ternary silicon alloy, such as any one of Zn-Si-P, Cu-Si-P, Al-Si-P or In-Si-P. Preferably, the negative electrode active material is a quaternary silicon alloy, such as any one of Zn-Cu-Si-P, Zn-Al-Si-P, Zn-In-Si-P, Cu-Al-Si-P, Cu-In-Si-P or Al-In-Si-P. Preferably, the negative electrode active material is a five-element silicon alloy, such as any one of Zn-Cu-Al-Si-P, Zn-Cu-In-Si-P, Zn-Al-In-Si-P, Cu-Al-In-Si-P or Zn-Cu-Al-In-Si-P.

[0041] The second aspect of the present invention discloses a method for preparing a sulfide all-solid-state battery negative electrode, comprising the following steps: Step 1: weigh a certain amount of zinc powder (Zn), copper powder (Cu), aluminum powder (Al), indium powder (In), or a mixture of several of them, silicon (Si) powder or silicon particles, and red phosphorus (P) according to the designed molar ratio and put them into a mortar for premixing, and then add the premixed powders into a stainless steel ball mill filled with argon. Add a certain amount of stainless steel ball milling beads into the ball mill, and after ball milling at a specific speed to obtain the negative electrode active material, take it out for use.

[0042] Step 2: Take a certain amount of the above-mentioned negative electrode active material, add a certain mass of conductive additive, manually mix the above-mentioned silicon alloy negative electrode active material with conductive additive, then transfer it to a ball mill filled with argon, add a certain amount of stainless steel ball milling beads and ball mill for a certain time to obtain silicon alloy powder evenly mixed with the conductive additive, and then take it out for use.

[0043] Step 3, take a certain amount of the silicon alloy powder uniformly mixed with the conductive additive, add a certain amount of binder and a certain amount of deionized water to prepare a negative electrode slurry. The negative electrode slurry is transferred to a ball mill filled with argon and ball milled at a speed of 300-350 rpm for 60 min on a planetary ball mill. Then, the mixed slurry is coated on the surface of a clean copper foil and transferred to a vacuum oven for drying. The dried pole piece is taken out and the pole piece is cut into a silicon alloy negative electrode with a diameter of 12 mm by a punching machine, which is a sulfide all-solid-state battery negative electrode.

[0044] Preferably, in step 1, the ball milling time for preparing the negative electrode active material is 10 to 15 hours, and the ball milling speed is 450 to 800 rpm. If the speed is too low, it is difficult to provide the composite energy of the multi-substances, and if the speed is too high, excessive energy will be generated, resulting in overheating and failure of the raw material.

[0045] Preferably, when preparing the alloy material, the weight ratio of the mixed material to the ball milling beads is 1:(25-35).

[0046] Preferably, the silicon particles in the raw material are nano-silicon or micro-silicon, and the particle size of Si selected can be 30 nm, 100 nm, 200 nm, 700 nm, 1 μm, 3 μm, etc.

[0047] Preferably, the negative electrode slurry has a solid content of 30%.

[0048] In some embodiments of the present invention, the metal-Si-P is in powder or granular form.

[0049] In the present invention, the silicon alloy negative electrode active material is prepared by mechanical ball milling, and the reaction process is easy to control, green and environmentally friendly, and suitable for large-scale preparation. The introduced metal elements and alloying elements can widen the interplanar spacing of silicon, thereby improving the carrier transfer rate. At the same time, the alloy material can maintain the crystal structure during the charge and discharge cycle, thereby inhibiting the volume expansion of silicon and effectively alleviating the stress damage inside the negative electrode during the cycle.

[0050] Based on the above functions, when the silicon alloy negative electrode material is used in sulfide all-solid-state batteries, it can improve the lithium ion diffusion coefficient and electronic conductivity of the negative electrode, and at the same time improve the cycle stability of the silicon negative electrode, thereby improving the rate performance and cycle life of the all-solid-state battery.

[0051] The third aspect of the present invention discloses an application of a sulfide all-solid-state battery silicon alloy negative electrode for preparing a sulfide all-solid-state battery. The solid electrolyte used in the sulfide all-solid-state battery is Li6PS5Cl (LPSC), Li 5.5 PS 4.5 Cl 1.5 and Li 10 GeP2S 12 One or more of .

[0052] In some schemes of the present invention, a sulfide all-solid-state battery silicon alloy negative electrode sheet preparation process is as follows: weigh 3 g of Zn, Si and P powders in a pre-designed molar ratio and mix them evenly by hand, then add them to a stainless steel ball mill filled with argon, add 75 g of stainless steel ball milling beads with a diameter of 6 mm, and ball mill for 10 h at a ball milling speed of 500 rpm to obtain a Zn-Si-P alloy negative electrode active material, and take out the obtained alloy negative electrode active material for use. The above alloy negative electrode active material is added to a mortar, and then graphite is weighed and mixed evenly by hand according to a mass ratio of alloy powder: graphite = 8:1, and then ball milled in a stainless steel ball mill filled with argon for 5 h to obtain a negative electrode active material evenly mixed with graphite. Then, in a ball mill, the above negative electrode active material evenly mixed with graphite and a polyacrylic acid binder are prepared into a uniform slurry with a solid content of 30%. The above ball-milled slurry is coated on a 12 μm thick copper current collector by a doctor blade method. Among them, the negative electrode loading is set to 0.4~2 mg / cm 2 The coating thickness is 60-300 μm. Finally, the above-mentioned electrode is kept in a vacuum drying oven at 80°C for 12 h to obtain the final alloy negative electrode.

[0053] In some embodiments of the present invention, the preparation process of the all-solid-state half-cell based on the sulfide all-solid-state battery silicon alloy negative electrode comprises the following steps: (1) The metal-Si-P negative electrode active material, conductive additive, and polyacrylic acid binder were prepared in a mass ratio of 8:1:1, and a certain amount of deionized water was added to form a negative electrode slurry with a solid content of 30%. The mixture was further ball milled in a planetary ball mill at a speed of 300-350 rpm for 60 min to obtain a uniform silicon negative electrode slurry.

[0054] (2) The slurry in (1) was evenly coated on a 12 μm thick copper foil using an automatic coating machine, and the alloy negative electrode loading was set to 0.4-2 mg / cm 2 The coating thickness is set to 60-300 μm, and then placed in a vacuum oven to dry to remove water. After drying, the silicon negative electrode pieces with a diameter of 12 mm are cut, the mass of the pieces is weighed, and the active material loading is calculated.

[0055] (3) The electrode sheet prepared in (2) was transferred to a glove box filled with argon gas to assemble the sulfide all-solid-state battery. First, 100 mg of sulfide solid electrolyte Li6PS5Cl (LPSC) was weighed and poured into a polyetheretherketone (PEEK) annular sleeve with a diameter of 12 mm, and then the solid electrolyte was pressed at 175 MPa for 1 min to obtain a solid electrolyte sheet. The negative electrode sheet prepared in (2) was placed in a mold and co-pressed with LPSC, pre-pressed at 175 MPa for 1 min, and then pressurized to 350 MPa and maintained for 5 min. After the pressure was maintained, it was unloaded. Then, indium with a diameter of 12 mm and a thickness of 100 μm and ultra-thin lithium with a thickness of 60 μm were placed in turn on the other side of the mold, and the mold was installed in the mold frame and pressurized to 175 MPa for 1 min, so that lithium and indium formed lithium-indium alloy under pressure, and then slowly unloaded to 75 MPa and tightened the screws. The sulfide all-solid-state half-cell was assembled.

[0056] (4) The half-cell assembled in (3) was subjected to electrochemical performance test. + The constant current charge and discharge test was carried out in the range of 1.5V / Li, and the theoretical capacity was set to 3200 mAh / g. The pre-cycle was performed at a rate of 0.1 C for 3 cycles, and then a long cycle test was performed at a rate of 1 C.

[0057] Electrochemical impedance spectroscopy (EIS) tests were performed before the start of the cycle, after 1 cycle, 10 cycles, and 50 cycles to study the internal interface stability of the negative electrode, with a test frequency range of 1 MHz to 0.1 Hz. Before the start of the cycle and after 50 cycles, the battery was disassembled and the surface morphology of the negative electrode was observed using a scanning electron microscope (SEM) to study the changes in the negative electrode at different cycle stages.

[0058] The following is further described in conjunction with specific embodiments.

[0059] Example 1 According to the molar ratio of Zn:Si:P=1:12:3, 0.396 g of zinc powder (Zn), 2.043 g of silicon powder (Si) and 0.561 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnSi 12 P3 alloy powder was taken out for later use. Weigh 480 mg of ZnSi 12P3 alloy powder was added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0060] Figure 1 The XRD patterns of Example 1, Comparative Example 2 and Comparative Example 3 of the present invention are shown in Figure 1. Through XRD analysis, it can be seen that the characteristic peaks of Si and Zn exist simultaneously in Comparative Example 2 and Comparative Example 3, indicating that there is no alloying. The characteristic peak of Zn disappears in the characteristic peak of Example 1, and only ZnSi 12 P3 alloy peak, indicating that ZnSi 12 P3 alloy was successfully prepared. Figure 2 The ZnSi mixed with graphite prepared in Example 1 12 SEM and EDS spectra of P3 alloy powder show that ZnSi 12 P3 alloy powder is uniformly mixed with graphite.

[0061] The ZnSi mixed with graphite 12 P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was coated on the clean Cu current collector surface by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0062] The prepared ZnSi 12 The P3 alloy negative electrode is used in the sulfide all-solid-state battery. The preparation process of the battery includes the following steps: Step 1: Use a manual punching machine to cut out a 12 mm diameter electrode from the electrode coated with the slurry. Transfer the cut electrode to a glove box filled with argon for later use.

[0063] Step 2, weigh 100 mg of sulfide solid electrolyte LPSC and pour it into a polyetheretherketone (PEEK) annular sleeve with a diameter of 12 mm, and then press the solid electrolyte at 175 MPa for 1 min to obtain a solid electrolyte sheet. The negative electrode sheet prepared in (2) is placed in the mold and co-pressed with LPSC, pre-pressed at 175 MPa for 1 min, and then pressurized to 350 MPa for 5 min, and unloaded after the pressure is maintained. Then, indium with a diameter of 12 mm and a thickness of 100 μm and ultra-thin lithium with a thickness of 60 μm are placed in the other side of the mold in sequence, and the mold is installed in the mold frame and pressurized to 175 MPa for 1 min, so that lithium and indium form lithium-indium alloy under pressure, and then slowly unloaded to 75 MPa and tightened The screws are assembled, and the sulfide all-solid-state half-cell is assembled.

[0064] Step 3: Test the electrochemical performance of the half-cell assembled in step 2. + The constant current charge and discharge test was carried out in the range of 1.5V / Li, and the theoretical capacity was set to 3200 mAh / g. The pre-cycle was performed at a rate of 0.1 C for 3 cycles, and then a long cycle test was performed at a rate of 1 C.

[0065] Electrochemical impedance spectroscopy (EIS) tests were performed before the start of the cycle, after 1 cycle, 10 cycles, and 50 cycles to study the internal interface stability of the negative electrode, with a test frequency range of 1 MHz to 0.1 Hz. Before the start of the cycle and after 50 cycles, the battery was disassembled and the surface morphology of the negative electrode was observed using a scanning electron microscope (SEM) to study the changes in the negative electrode at different cycle stages. Figure 3 The long cycle performance comparison diagram of the half-cells assembled using Example 1, Comparative Example 1 and Comparative Example 2 at a current density of 1 C. It can be seen that compared with Comparative Example 1 and Comparative Example 2, Example 1 has better cycle stability. Figure 4 This is a comparison chart of the electronic conductivity of Example 1 of the present invention, Comparative Example 1 and Comparative Example 2 tested by the chronoamperometry. It can be seen that compared with Comparative Example 1 and Comparative Example 2, the electronic conductivity of Example 1 is greatly improved. Figure 5 This is a comparison chart of the lithium ion diffusion coefficients of Example 1 of the present invention, Comparative Example 1 and Comparative Example 2 tested by the constant current intermittent titration method. It can be seen that compared with Comparative Example 1 and Comparative Example 2, the lithium ion diffusion coefficient of Example 1 is greatly improved.

[0066] Example 2 According to the molar ratio of Zn:Si:P=1:7:3, 0.552 g of zinc powder (Zn), 1.662 g of silicon powder (Si) and 0.786 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnSi7P3 alloy powder, which was taken out for use. 480 mg of ZnSi7P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the ZnSi7P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for use.

[0067] The prepared ZnSi7P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and then deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0068] The prepared ZnSi7P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0069] Example 3 According to the molar ratio of Zn:Si:P=1:2:3, 0.915 g of zinc powder (Zn), 0.786 g of silicon powder (Si) and 1.299 g of phosphorus powder (P) were weighed and mixed manually. Then the mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and milled at 500 rpm for 10 hours to obtain ZnSi2P3 alloy powder, which was taken out and set aside. 480 mg of ZnSi2P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the ZnSi2P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for later use.

[0070] The prepared ZnSi2P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0071] The prepared ZnSi2P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0072] Example 4 According to the molar ratio of Cu:Si:P=1:12:3, 0.386 g of copper powder (Cu), 2.049 g of silicon powder (Si) and 0.565 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain CuSi 12 P3 alloy powder was taken out and set aside. Weigh 480 mg of CuSi 12 P3 alloy powder was added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use. Figure 6 The XRD patterns of Example 4, Comparative Example 4 and Comparative Example 5 of the present invention are shown in Figure 1. Through XRD analysis, it can be seen that the characteristic peaks of Si and Cu exist simultaneously in Comparative Example 4 and Comparative Example 5, indicating that there is no alloying. The characteristic peak of Cu disappears in the characteristic peak of Example 4, and only CuSi 12 P3 alloy peak, indicating CuSi 12 P3 alloy was successfully prepared. Figure 7 The CuSi mixed with graphite prepared in Example 4 12 SEM and EDS spectra of P3 alloy powder show that CuSi 12 P3 alloy powder is uniformly mixed with graphite.

[0073] The CuSi mixed with graphite 12P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed slurry. The slurry was evenly coated on the current collector by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0074] The prepared CuSi 12 The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0075] Example 5 According to the molar ratio of Cu:Si:P=1:7:3, 0.540 g of copper powder (Cu), 1.671 g of silicon powder (Si) and 0.789 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain CuSi7P3 alloy powder, which was taken out and set aside. 480 mg of CuSi7P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the CuSi7P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for later use.

[0076] The CuSi7P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0077] The prepared CuSi7P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0078] Example 6 According to the molar ratio of Zn:Si:P=4:12:3, 1.134 g of zinc powder (Zn), 1.461 g of silicon powder (Si) and 0.405 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain Zn4Si 12 P3 alloy powder was taken out and set aside. Weigh 480 mg of Zn4Si 12 P3 alloy powder was added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0079] The Zn4Si mixed with graphite 12 P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the current collector by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0080] The prepared Zn4Si 12 The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0081] Example 7 According to the molar ratio of Zn:Si:P=1:4:3, 0.726 g zinc powder (Zn), 1.245 g silicon powder (Si) and 1.029 g phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnSi4P3 alloy powder, which was taken out and set aside. 480 mg of ZnSi4P3 alloy powder was weighed and added to a mortar, and then 60 mg of conductive carbon black was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the ZnSi4P3 alloy powder mixed with the conductive carbon black was taken out and stored in a glove box filled with argon for later use.

[0082] The ZnSi4P3 alloy powder uniformly mixed with the conductive carbon black and 60 mg of polyvinylidene fluoride binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the current collector by a doctor blade method, and the negative electrode loading was set to 0.4 mg / cm 2 The coating thickness is 60 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0083] The prepared ZnSi4P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0084] Example 8 According to the molar ratio of Al:Si:P=3:12:2, 0.507 g of aluminum powder (Al), 2.106 g of silicon powder (Si) and 0.387 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and milled at a speed of 500 rpm for 10 hours to obtain Al3Si 12 P2 alloy powder was taken out and set aside. Weigh 480 mg of Al3Si 12 P2 alloy powder was added to a mortar, and then 60 mg of carbon fiber was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the Al3Si 12 The P2 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0085] The Al3Si mixed with carbon fiber 12 P3 alloy powder and 60 mg of styrene-butadiene rubber binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 1 mg / cm 2 The coating thickness is 180 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0086] The prepared Al3Si 12 The P2 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0087] Example 9 According to the molar ratio of In:Si:P=1:12:3, 0.633 g of indium powder (In), 1.857 g of silicon powder (Si) and 0.513 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain InSi 12 P3 alloy powder was taken out and set aside. Weigh 450 mg of InSi 12 P3 alloy powder was added to a mortar, and then 25 mg of carbon nanotube graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the InSi 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0088] The InSi mixed with carbon nanotube graphite 12 P3 alloy powder and 25 mg of styrene-butadiene rubber polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the current collector by blade coating, and the negative electrode loading was set to 2 mg / cm 2 The coating thickness is 300 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0089] The prepared InSi 12The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0090] Example 10 According to the molar ratio of Al:Si:P=1:7:3, 0.255 g of aluminum powder (Al), 1.863 g of silicon powder (Si) and 0.882 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 450 rpm for 15 hours to obtain AlSi7P3 alloy powder, which was taken out and set aside. 480 mg of AlSi7P3 alloy powder was weighed and added to a mortar, and then 30 mg of graphene was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the AlSi7P3 alloy powder mixed with graphene and graphite was taken out and stored in a glove box filled with argon for later use.

[0091] The AlSi7P3 alloy powder mixed with graphene graphite and 30 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.4 mg / cm 2 The coating thickness is 60 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0092] The prepared AlSi7P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0093] Embodiment 11 According to the molar ratio of In:Si:P=1:7:3, 0.852 g of indium powder (In), 1.458 g of silicon powder (Si) and 0.689 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 800 rpm for 12 hours to obtain InSi7P3 alloy powder, which was taken out and set aside. 480 mg of InSi7P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the InSi7P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for later use.

[0094] The InSi7P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0095] The prepared InSi7P3 alloy negative electrode was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0096] Example 12 According to the molar ratio of Al:Si:P=1:2:3, 0.459 g of aluminum powder (Al), 0.957 g of silicon powder (Si) and 1.584 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at a speed of 500 rpm for 10 hours to obtain AlSi2P3 alloy powder, which was taken out and set aside. 480 mg of AlSi2P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to ball mill for 5 hours. After the ball milling was completed, the AlSi2P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for later use.

[0097] The AlSi2P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0098] The prepared AlSi2P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0099] Embodiment 13 According to the molar ratio of In:Si:P=1:2:3, 1.305 g of indium powder (In), 0.639 g of silicon powder (Si) and 1.059 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain InSi2P3 alloy powder, which was taken out and set aside. 480 mg of InSi2P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the InSi2P3 alloy powder mixed with graphite was taken out and stored in a glove box filled with argon for later use.

[0100] The InSi2P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0101] The prepared InSi2P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0102] Embodiment 14 According to the molar ratio of Zn:Cu:Si:P=1:1:12:3, 0.351 g of zinc powder (Zn), 0.339 g of copper powder (Cu), 1.806 g of silicon powder (Si) and 0.498 g of phosphorus powder (P) were weighed and mixed manually. Then the mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnCuSi 12 P3 alloy powder was taken out and set aside. Weigh 480 mg of ZnCuSi 12 P3 alloy powder was added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0103] The above ZnCuSi mixed with graphite 12 P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0104] The prepared ZnCuSi 12 The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0105] Embodiment 15 According to the molar ratio of Zn:Al:Si:P=1:1:12:3, 0.375 g of zinc powder (Zn), 0.156 g of aluminum powder (Al), 1.935 g of silicon powder (Si) and 0.534 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnAlSi 12 P3 alloy powder was taken out and set aside. Weigh 480 mg of ZnAlSi 12P3 alloy powder was added to a mortar, followed by 60 mg of graphite and manual mixing. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0106] The ZnAlSi mixed with graphite 12 P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. Deionized water was added to adjust the solid content of the slurry to 30%. The slurry was placed in a planetary ball mill and ball milled at 350 rpm for 60 minutes. After ball milling, the slurry was evenly coated on the current collector by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0107] The prepared ZnAlSi 12 The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0108] Example 16 According to the molar ratio of Zn:In:Si:P=1:1:12:3, 0.321 g of zinc powder (Zn), 0.564 g of indium powder (In), 1.659 g of silicon powder (Si) and 0.456 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, followed by 75 g of stainless steel ball milling beads with a diameter of 6 mm. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnInSi 12 P3 alloy powder was taken out and set aside. Weigh 480 mg of ZnInSi 12 P3 alloy powder was added to a mortar, followed by 60 mg of graphite and manual mixing. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. 12 The P3 alloy powder was taken out and stored in a glove box filled with argon for future use.

[0109] The ZnInSi mixed with graphite 12P3 alloy powder and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by blade coating, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0110] The prepared ZnInSi 12 The P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0111] Embodiment 17 According to the molar ratio of Zn:Cu:Al:Si:P=1:1:1:4:3, 0.543 g of zinc powder (Zn), 0.528 g of copper powder (Cu), 0.225 g of aluminum powder (Al), 0.933 g of silicon powder (Si) and 0.771 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 600 rpm for 10 hours to obtain ZnCuAlSi4P3 alloy powder, which was taken out and set aside. 480 mg of ZnCuAlSi4P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling is completed, the ZnCuAlSi4P3 alloy powder uniformly mixed with graphite is taken out and stored in a glove box filled with argon for later use.

[0112] The ZnCuAlSi4P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0113] The prepared ZnCuAlSi4P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0114] Embodiment 18 According to the molar ratio of Zn:Cu:Al:In:Si:P=1:1:1:1:4:3, 0.411 g of zinc powder (Zn), 0.402 g of copper powder (Cu), 0.171 g of aluminum powder (Al), 0.726 g of indium powder (In), 0.708 g of silicon powder (Si) and 0.585 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 10 hours to obtain ZnCuAlInSi4P3 alloy powder, which was taken out and set aside. 480 mg of ZnCuAlInSi4P3 alloy powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling is completed, the ZnCuAlInSi4P3 alloy powder uniformly mixed with graphite is taken out and stored in a glove box filled with argon for later use.

[0115] The ZnCuAlInSi4P3 alloy powder mixed with graphite and 60 mg of polyacrylic acid binder were added to a ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0116] The prepared ZnCuAlInSi4P3 alloy negative electrode is used in a sulfide all-solid-state battery, and all the steps are the same as in Example 1.

[0117] Comparative Example 1 Take 160 mg of silicon powder (Si), 20 mg of graphite and 20 mg of polyacrylic acid binder, add them to the ball mill, add deionized water to adjust the solid content of the slurry to 30%. Place the ball mill in a planetary ball mill and mill at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry is evenly coated on the surface of the Cu current collector by blade coating, and the negative electrode loading is set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0118] The prepared silicon negative electrode is applied to a sulfide all-solid-state battery, and all steps are the same as in Example 1.

[0119] Comparative Example 2 According to the molar ratio of Zn:Si:P=1:12:3, 0.396 g of zinc powder (Zn), 2.04 g of silicon powder (Si) and 0.564 of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 3 hours to obtain a Zn-12Si-3P-3h mixed powder, which was taken out and set aside. 480 mg of Zn-12Si-3P-3h mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the Zn-12Si-3P-3h mixed powder mixed with graphite was taken out and stored in a glove box filled with argon for use.

[0120] The Zn-12Si-3P-3h mixed powder and 60 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0121] The prepared Zn-12Si-3P-3h electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0122] Comparative Example 3 According to the molar ratio of Zn:Si:P=1:12:3, 0.396 g of zinc powder (Zn), 2.04 g of silicon powder (Si) and 0.564 of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 6 hours to obtain a Zn-12Si-3P-6h mixed powder, which was taken out and set aside. 480 mg of Zn-12Si-3P-6h mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the Zn-12Si-3P-6h mixed powder mixed with graphite was taken out and stored in a glove box filled with argon for use.

[0123] The Zn-12Si-3P-6h mixed powder and 60 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0124] The prepared Zn-12Si-3P-6h electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0125] Comparative Example 4 According to the molar ratio of Cu:Si:P=1:12:3, 0.387 g of copper powder (Cu), 2.049 g of silicon powder (Si) and 0.564 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 3 hours to obtain a Cu-12Si-3P-3h mixed powder, which was taken out for use. 480 mg of the Cu-12Si-3P-3h mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to ball mill for 5 hours. After the ball milling was completed, the Cu-12Si-3P-3h powder mixed with graphite was taken out and stored in a glove box filled with argon for use.

[0126] The Cu-12Si-3P-3h powder mixed with graphite and 60 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0127] The prepared Cu-12Si-3P-3h electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0128] Comparative Example 5 According to the molar ratio of Cu:Si:P=1:12:3, 0.387 g of copper powder (Cu), 2.049 g of silicon powder (Si) and 0.564 g of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 500 rpm for 6 hours to obtain a Cu-12Si-3P-6h mixed powder, which was taken out for use. 480 mg of the Cu-12Si-3P-6h mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling was completed, the Cu-12Si-3P-6h powder mixed with graphite was taken out and stored in a glove box filled with argon for use.

[0129] The Cu-12Si-6P-3h powder mixed with graphite and 60 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0130] The prepared Cu-12Si-3P-6h electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0131] Comparative Example 6 According to the molar ratio of Zn:Si:P=1:12:3, 0.396 g of zinc powder (Zn), 2.04 g of silicon powder (Si) and 0.564 of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 300 rpm for 10 hours to obtain a Zn-12Si-3P-300r mixed powder, which was taken out and set aside. 480 mg of Zn-12Si-3P-300r mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling is completed, the Zn-12Si-3P-300r mixed powder uniformly mixed with graphite is taken out and stored in a glove box filled with argon for later use.

[0132] The Zn-12Si-3P-300r mixed powder and 60 mg polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0133] The prepared Zn-12Si-3P-300r electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0134] Comparative Example 7 According to the molar ratio of Zn:Si:P=1:12:3, 0.396 g of zinc powder (Zn), 2.04 g of silicon powder (Si) and 0.564 of phosphorus powder (P) were weighed and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon, and then 75 g of stainless steel ball milling beads with a diameter of 6 mm were added. The ball mill was placed on a planetary ball mill and ball milled at 1000 rpm for 10 hours to obtain a Zn-12Si-3P-1000r mixed powder, which was taken out and set aside. 480 mg of Zn-12Si-3P-1000r mixed powder was weighed and added to a mortar, and then 60 mg of graphite was added and mixed manually. The mixed powder was added to a stainless steel ball mill filled with argon and continued to be ball milled for 5 hours. After the ball milling is completed, the Zn-12Si-3P-1000r mixed powder uniformly mixed with graphite is taken out and stored in a glove box filled with argon for later use.

[0135] The Zn-12Si-3P-1000r mixed powder and 60 mg of polyacrylic acid binder were added to the ball mill, and deionized water was added to adjust the solid content of the slurry to 30%. The ball mill was placed in a planetary ball mill and milled at 350 rpm for 60 minutes to obtain a uniformly mixed negative electrode slurry. The slurry was evenly coated on the surface of the Cu current collector by a doctor blade method, and the negative electrode loading was set to 0.8 mg / cm 2 The coating thickness is 150 μm. Subsequently, the coated electrode sheet is placed in a vacuum drying oven at 80° C. for 12 hours to remove water, thereby obtaining a negative electrode sheet.

[0136] The prepared Zn-12Si-3P-1000r electrode sheet was used in a sulfide all-solid-state battery, and all the steps were the same as in Example 1.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a sulfide all-solid-state battery silicon alloy negative electrode, characterized in that: The following steps are involved: Step 1, mixing metal powder, silicon powder and phosphorus powder and then ball milling to obtain a negative electrode active material; the metal powder is any one of zinc powder, copper powder, aluminum powder or indium powder or a mixture of several thereof; Step 2, mixing the negative electrode active material and the conductive additive, and obtaining a mixed powder of the conductive additive and the negative electrode active material after ball milling; Step 3, adding a binder and a solvent to the mixed powder obtained in step 2 to obtain a mixture, and ball-milling the mixture to obtain a uniform negative electrode slurry; Step 4: coating the negative electrode slurry on the surface of the current collector, drying and cutting to obtain a silicon alloy negative electrode sheet.

2. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 1, the mixing molar ratio of the metal powder, silicon powder and phosphorus powder is (1-4): (2-12): (2-3).

3. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 1, when the metal powder consists of two or more types of metals, they are mixed in an equal molar ratio.

4. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 1, the ball milling time is 10-15 h, and the rotation speed is 450-800 rpm.

5. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 1, the silicon powder is nano silicon or micro silicon.

6. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 2 and step 3, the mixing mass ratio of the negative electrode active material, the conductive additive and the binder is (8~9): (1~0.5): (1~0.5).

7. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 4, the loading amount of the negative electrode slurry on the current collector is 0.4-2 mg / cm 2 The current collector is copper foil, and the coating thickness of the negative electrode slurry is 60 to 300 μm.

8. The method for preparing a sulfide all-solid-state battery silicon alloy negative electrode according to claim 1, characterized in that: In step 2, the conductive additive is graphite, conductive carbon black, carbon fiber, carbon nanotube or graphene; in step 3, the binder is polyacrylic acid, polyvinylidene fluoride or styrene-butadiene rubber.

9. A sulfide all-solid-state battery silicon alloy negative electrode prepared by the preparation method according to claim 1, characterized in that: The invention comprises a current collector, on which a negative electrode slurry is coated, wherein the negative electrode slurry is composed of a negative electrode active material, a binder and a conductive additive; the negative electrode active material is obtained by mechanical ball milling and alloying of metal powder, silicon powder and phosphorus powder; The metal is any one of zinc, copper, aluminum or indium or a mixture of several of them.

10. An application of the sulfide all-solid-state battery silicon alloy negative electrode according to claim 9, characterized in that: Used in sulfide all-solid-state batteries.

Citation Information

Patent Citations

  • Zn-Ge-Cu-Si-P high-entropy alloy material used as negative electrode of lithium ion battery and preparation method for Zn-Ge-Cu-Si-P high-entropy alloy material

    CN113846258A

  • High-entropy phosphide for sodium ion battery negative electrode material and preparation method of high-entropy phosphide

    CN118083928A

  • Carbon-doped porous medium-entropy alloy lithium ion battery negative electrode material and preparation method thereof

    CN118431442A

  • Composite electrode containing sulfide-based solid electrolyte and all-solid-state battery using same

    US20210013541A1

Cited By

  • Negative electrode material, preparation method thereof and secondary battery

    CN121583918A